Impact of the implantable cardioverter defibrillator on confidence to undertake physical activity in inherited heart disease: A cross-sectional study. (1st December 2017) - Sweeting, Joanna; Ball, Kylie; McGaughran, Julie; Atherton, John; Semsarian, Christopher; Ingles, Jodie
Abstract: Background: Physical activity is associated with improved quality of life. Patients with an implantable cardioverter defibrillator (ICD) face unique clinical and psychological challenges. Factors such as fear of ICD shock may negatively impact on physical activity, while a sense of protection gained from the ICD may instil confidence to be active. Aim: We aimed to examine the impact of an ICD on physical activity levels and factors associated with amount of activity. Methods: Two cross-sectional studies were conducted. Accelerometer data (seven-day) was collected in March–November 2015 for 63 consecutively recruited hypertrophic cardiomyopathy patients, with or without an ICD, aged ⩾18 years. A survey study was conducted in July–August 2016 of 155 individuals aged ⩾18 years with an inherited heart disease and an ICD in situ. Results: Based on the International Physical Activity Questionnaire, mean leisure time physical activity was 239 ± 300 min/week with 51% meeting physical activity guidelines. Accelerometry showed that mean moderate–vigorous physical activity was the same for patients with and without an ICD (254 ± 139 min/week versus 300 ± 150 min/week, p =0.23). Nearly half of survey participants ( n =73) said their device made them more confident to exercise. Being anxious about ICD shocks was the only factor associated with not meeting physical activity guidelines. Conclusions: Patients with inherited heart disease adjust differently to their ICD device, and for many it has no impact on physical activity. Discussion regarding the appropriate level of physical activity and potential barriers will ensure best possible outcomes in this unique patient group.